2021
DOI: 10.1111/medu.14575
|View full text |Cite
|
Sign up to set email alerts
|

‘Nurses whisper.’ Identities in nurses’ patient safety narratives of nurse‐trainee doctors’ interactions

Abstract: Context Nurses are integral to patient safety, but little is known about their narrative constructions of identity in relation to their dyadic interactions with trainee doctors about patient safety and competence during the trajectory of a medical career. Aim We sought to examine how identities are constructed by experienced nurses in their narratives of patient safety encounters with trainee doctors. Methods Our qualitative study gathered narrative data through semi‐structured interviews with nurses of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…With professional roles and occupational boundaries being flexible and malleable, when working across these boundaries, cooperation can occur. Cooperation comes in many forms, including doctors deferring to nurses' experience and expertise, resulting in productive interprofessional relationships and enhanced patient outcomes ( 2 , 5 ). Thus, research has shown how newly qualified doctors learn from nurses who have an important role in junior doctors' procedural skill development, alongside their professional socialization, as they navigate the complexities of hospital cultures and practices ( 6 ).…”
Section: Diversity Challenges Across Healthcare Professional Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…With professional roles and occupational boundaries being flexible and malleable, when working across these boundaries, cooperation can occur. Cooperation comes in many forms, including doctors deferring to nurses' experience and expertise, resulting in productive interprofessional relationships and enhanced patient outcomes ( 2 , 5 ). Thus, research has shown how newly qualified doctors learn from nurses who have an important role in junior doctors' procedural skill development, alongside their professional socialization, as they navigate the complexities of hospital cultures and practices ( 6 ).…”
Section: Diversity Challenges Across Healthcare Professional Groupsmentioning
confidence: 99%
“…Rather, subjectivity of what is real centers around discursive processes, including who is talking, to whom they are conversing, for what purpose , and so on. To know something is to attend to what is being said and how it is conveyed ( 5 , 36 ). Here there are no causal links between constructs, no regular patterns or universal laws.…”
Section: Diversity Challenges Of Research Approachesmentioning
confidence: 99%
“…Previous studies have shown that nurses can act as practitioners of patient safety and educators of medical residents [ 15 , 16 ]. Their observations and feedback to medical residents and senior doctors can make patients safer and lead to more effective patient care [ 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that nurses can act as practitioners of patient safety and educators of medical residents [ 15 , 16 ]. Their observations and feedback to medical residents and senior doctors can make patients safer and lead to more effective patient care [ 15 , 17 , 18 , 19 ]. The level of nurses’ contributions to physicians’ education can differ depending on clinical situations, such as medical resources, the number of senior doctors, and the specialty of education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation